Penerapan Metode AHP (Analytical Hierarchy Process) Seleksi Atlet Pelajar Berkebutuhan Khusus Di Dinas Pemuda Dan Olaraga Kota Bengkulu - Hengky Pernanda; Siswanto Siswanto; Reno Supardi (Jurnal Media Infotama, 2026)
Technological advances currently play a crucial role in supporting various human activities, including the athlete selection process. Youth and Sports Office in Bengkulu City (Dispora) is responsible for developing student athletes with special needs to achieve success at the regional and international levels. However, the current selection process remains subjective and lacks a structured decision support system. This study aims to apply the Analytical Hierarchy Process (AHP) method to assist in making the selection process for student athletes with special needs more objective, measurable, and transparent. The criteria used include body posture (anthropometrics), age, medical tests, and track record of achievements. The application of the AHP has proven effective in improving the quality of decision-making, providing fairer selection opportunities that align with the characteristics of prospective student athletes with special needs.